2022
DOI: 10.1007/s11144-022-02171-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the best medium for experiments on chemical computation with Belousov–Zhabotinsky reaction and ferroin-loaded Dowex beads

Abstract: Our study is focused on identification of the best medium for future experiments on information processing with Belousov–Zhabotinsky reaction proceeding in Dowex beads with immobilized catalyst inside. The optimum medium should be characterized by long and stable nonlinear behavior, mechanical stability and should allow for control with electric potential. We considered different types of Dowex ion-exchange resins, bead distributions and various initial concentrations of substrates: malonic acid and 1,4-cycloh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this respect, networks of interacting chemical oscillators seem to be an interesting candidate for chemical computers. The recent results (Adamatzky et al, 2011;Holley et al, 2011;Szymanski et al, 2011;Adamatzky et al, 2012) demonstrated that networks of chemical oscillators can be easily assembled in experiments and studied for around a day (Muzika and Górecki, 2022). Such networks can be optimized to perform classification tasks and process information with the best possible use of the chemical medium.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, networks of interacting chemical oscillators seem to be an interesting candidate for chemical computers. The recent results (Adamatzky et al, 2011;Holley et al, 2011;Szymanski et al, 2011;Adamatzky et al, 2012) demonstrated that networks of chemical oscillators can be easily assembled in experiments and studied for around a day (Muzika and Górecki, 2022). Such networks can be optimized to perform classification tasks and process information with the best possible use of the chemical medium.…”
Section: Introductionmentioning
confidence: 99%